2023
DOI: 10.3390/v15040976
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Effect of Nirmatrelvir/Ritonavir during COVID-19 Pandemic Real-World Data

Abstract: Introduction: Vaccination against SARS-CoV-2 and the prevalence of Omicron variants have reduced the risk of the severe clinical progress of COVID-19. However, the risk of breakthrough infections has increased, and early administration of an effective antiviral treatment is significant in order to prevent the severe progression of COVID-19 in vulnerable patients with comorbidities. Patients and methods: Adults with confirmed SARS-CoV-2 infection were included in a matched-pair retrospective study based on age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In our study, we had no treatment discontinuations due to side effects for both treatment arms. We did not record minor adverse events, not dictating treatment discontinuation, but regulatory studies showed that both remdesivir and NMV/r seem to be well tolerated, with low rates of treatment discontinuation [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we had no treatment discontinuations due to side effects for both treatment arms. We did not record minor adverse events, not dictating treatment discontinuation, but regulatory studies showed that both remdesivir and NMV/r seem to be well tolerated, with low rates of treatment discontinuation [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mazzitelli et al, in Italy, compared 3RDV to no treatment in a large real-world cohort and found that the use of 3RDV would reduce the risk of hospitalization by 95% and the duration of positivity and symptoms by eight and five days, respectively [ 39 ]. Similarly, a recent observational study from Greece compared NMV/r to no treatment and showed that in the first group, only 1.5% required eventual hospitalization, compared to a staggering 55.5% in the control group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers should educate patients on the correct dosage and duration of Azvudine. Compared to other effective antiviral drugs, such as Paxlovid, the Greek study found that compliance was 97.5 %, which was attributed to patients voluntarily stopping treatment two or three days after starting treatment due to significant clinical improvement (doctors recommended 5 days of treatment) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most heterogeneous results were observed for disease progression, with some studies reporting a statistically significant protective effect of NR, while other studies T A B L E 2 Comparison of the pooled risk ratios (RR) for the different outcomes, including sensitivity analyses and subgroup analysis. Included studies were 34,38,40,41,43,46,47,50,[52][53][54]58,[62][63][64][65][66] observed (nonsignificant) higher risk of progression with administration of NR.…”
Section: Heterogeneity Of the Included Studiesmentioning
confidence: 99%